Desain Sistem 5-Axis Robotic Arm untuk Otomatisasi Quality Control dengan Infrared - Habib Aufarizag; Handi Wilujeng Nugroho; Kurniawan Hamidi (Teknosia, 2025)
This study aims to design an optimized 5-Axis Robotic Arm system for Quality Control (QC) applications utilizing infrared sensor technology. The research process involved a comprehensive literature review to explore the latest developments in robotic systems and automation technologies. Benchmarking similar products was conducted to identify strengths and weaknesses as a foundation for innovation. The preparation of the Bill of Material (BoM), Operation Process Chart (OPC), and Assembly Chart (AC) was essential for systematic production planning. The final design was developed using Inventor 2024 software to ensure precision and component compatibility. The results demonstrate that the selection of aluminum materials, servo motors with a lifting capacity of up to 10 kg, Arduino Uno R3, and Pixy Cam significantly enhanced the system’s flexibility, durability, and efficiency. Structural modifications improved the mechanical stability and operational lifespan of the robotic arm. This system is expected to serve as an effective solution to improve the accuracy and speed of Quality Control processes in modern industrial environments.